Frequency of hemodynamic response to orthostatic stress in heart failure with reduced ejection fraction, associations with clinical blood pressure - D. N. Fedorova; A. E. Soloveva; M. Fudim; V. L. Galenko; A. V. Kozlenok; A. V. Berezina; S. V. Villevalde (Российский кардиологический журнал)
Aim. To assess hemodynamic response to active standing test (AST) with beat-to-beat blood pressure (BP) monitoring, their association with office BP and symptoms of orthostatic intolerance in patients with heart failure (HF).Material and methods. Outpatient HF patients with documented  left ventricular ejection  fraction <40%, followed   up in a HF center  and receiving optimal medical therapy, underwent AST with beat-to-beat  non-invasive BP monitoring.Hemodynamic response was assessed according to the European Federation of Autonomic Societies criteria.Results. The study included 87 patients (mean age, 57±10 years; men, 76%). Normal hemodynamic response to orthostatic stress was observed  in 36 (41,4%) patients. Pathological response prevailed during the first minute of orthostatic stress — initial orthostatic hypotension (OH) (n=29, 33,3%) and delayed BP recovery (n=18, 20,7%).  Classical OH was detected  in 4 (4,6%)  patients. There was no orthostatic hypertension, defined as an increase in systolic BP (SBP) ≥20 mm Hg. According to office BP, hypotension was observed in 19 (21,8%) patients (SBP <90 mm Hg in 4 patients and 90-100 mm Hg in 15), hypertension (SBP >140 mm Hg) in 11 (12,6%) patients. Pathological response to orthostatic stress were more often observed  in office  SBP >140 mm Hg compared  to SBP ≤140 mmHg (90,9% and 53,9%, p=0,020).Orthostatic intolerance was noted in 43 (49,4%) patients and were not associated with the level of office SBP (p=0,398) or pathological responses to orthostatic stress (p=0,758 for initial OH and p=0,248  for delayed  BP recovery).Conclusion. The pathological hemodynamic response in AST with beat-to-beat BP monitoring in ambulatory patients with HF is most often represented  by initial OH and delayed BP recovery associated  with office SBP >140 mmHg. The frequency of symptoms of orthostatic intolerance did not differ between groups depending on the presence of an inadequate response to orthostatic stress.